(untitled) (International Journal of Scientific Trends, 2026)
Аrticle analyzes issues related to the characterization of the offender’s personality in theft. In addition, the article reveals the key features of the personality of an individual who commits theft and highlights the aspects that distinguish the offender’s personality from the subject of this crime.